Flood Control with Retention Pond in Manjahlega Villages, Rancasari Sub District, Bandung - Herdian Bayu Ash Siddiq, Raden (International Journal of Psychosocial Rehabilitation, 2020)
Human activities in urban areas have a positive impact on development and economic progress. But on the other side, it caused environmental problems like floods and groundwater levels to decrease. Several areas in Bandung have become annual flood subscriptions caused by overflow from rivers or drainage. For example, it is Manjahlega Villages at Rancasari Sub District. In this area, floods always occur between 20 and 50 cm every year. From the results of the hydrological analysis, it was found that the area of retention ponds was 0.98 ha with a catchment area of 130 ha. A 2-year rain period of 85.98 mm produces a discharge of 9.5 m3/s, and a 10-year rain return period of 126.16 mm produces a discharge of 13.94 m3/s. The results of storm water management model (SWMM) modelling concluded that with the retention pond, overflow from drainage channels of the Manjahlega villages can be solved; these conditions can be optimized by adding drainage capacity and channel maintenance with periodic dredging.